NPK Levels and Application Methods on Productivity of Amorphophallus muelleri Blume in Intercropping System - Santosa, Edi; Susila, Anas Dinurrohman; Lontoh, Adolf Pieter; Mine, Yoko; Sugiyama, Nobuo (Jurnal Jamu Indonesia, 2016)
Underground corm of Amorphophallus muelleri Blume contained glucomannan, a raw material widely used in beverage, food and medicinal industries. In Indonesia, A. muelleri is grown under intercropping system, however, average corm production was considered low. The low productivity could be related to the low input of chemical fertilizers. Therefore, the effects of NPK fertilizers and methods of application on A. muelleri productivity were evaluated in the present study for intercropping system. Two experiments were conducted at Leuwikopo Experimental Farm, Bogor, Indonesia from 2010-2012 under canopy of coffee trees. First experiment was conducted using four levels of N, P, and K applications, i.e., N:P2O5:K2O at the rate 0:0:0, 100:60:80, 125:60:100 and 150:60:120 kg ha-1. In second experiment, N:P2O5:K2O fertilizers at the rate of 100:60:80 were applied by conventional (solid) and liquefied. Results of first experiment showed that application of N, P and K at rate of 100 kg, 60 kg, and 80 kg ha-1 produced fresh corm weight 636.3±91.7 g per plant or increased by 63% higher than control. However, higher rate of NPK application did not increase corm yield, possibly due to the occurrence of leaf discoloration. Higher rates of NPK also delayed harvest time 1 to 2 weeks compared with control and caused wide variation of corm size. Thus, excess application of NPK should be avoided for high productivity of A. muelleri. Second experiment showed that there was no significant different among methods of application on fresh corm weight, i.e., 413 g and 396 g from conventional and liquefied applications, respectively. These experiments conclude that application of NPK is important to enhance A. muelleri production in intercropping system.